Penerapan Strategi Promosi Taman Baca Masyarakat (TBM) “Teratak Tilerasi” di Pekanbaru - ., Asma Amirah; ., Sulis Setiawati; ., Nur Eliza; ., Nining Sudiar (CV. ITTC INDONESIA, 2023)
TBM is a place or place that is owned, managed and developed by the community as a place to provide information to the surrounding community. This study contains how the TBM promotion strategy. In addition, the establishment of TBM certainly has a purpose. This study aims to determine the promotion strategy of TBM Teratak Literacy Pekanbaru as well as to serve the community regarding information needs and provide a collection of books and educational activities. This research method uses a descriptive qualitative approach and data collection is done through observation, interviews and literature study. The results of this study indicate that TBM promotes through collaboration between schools, promotions through social media and literacy activities.